Can diffusion-weighted imaging add information in the evaluation of breast lesions considered suspicious on magnetic resonance imaging? - Guatelli,Camila Souza (2017)
Abstract Objective: To assess the role of diffusion-weighted imaging (DWI) in the evaluation of breast lesions classified as suspicious on magnetic resonance imaging (MRI), correlating the findings with the results of the histological analysis. Materials and Methods: This was a retrospective, descriptive study based on a review of the medical records of 215 patients who were submitted to MRI with DWI before undergoing biopsy at a cancer center. Apparent diffusion coefficient (ADC) values were calculated for each lesion, and the result of the histological analysis was considered the gold standard. Results: The mean age was 49 years. We identified 252 lesions, 161 (63.9%) of which were found to be malignant in the histological analysis. The mean ADC value was higher for the benign lesions than for the malignant lesions (1.50 × 10–3 mm2/s vs. 0.97 × 10−3 mm2/s), the difference being statistically significant (p < 0.001). The ADC cut-off point with the greatest sensitivity and specificity on the receiver operating characteristic curve was 1.03 × 10−3 mm2/s. When the DWI and conventional MRI findings were combined, the accuracy reached 95.9%, with a sensitivity of 95.7% and a specificity of 96.4%. Conclusion: The use of DWI could facilitate the characterization of breast lesions, especially those classified as BI-RADS 4, increasing the specificity and diagnostic accuracy of MRI.